A Novel Intervention Platform for Service Members With Subjective Cognitive Complaints: Implementation, Patient Participation, and Satisfaction - Sullivan, Katherine W; Law, Wendy A; Loyola, Laura; Knoll, Martin A; Shub, Daniel E; French, Louis M (Military medicine, 2020)
Program overview of a novel cognitive training platform at Walter Reed National Military Medical Center (WRNMMC) for service members with subjective cognitive complaints: analysis of patient participation, satisfaction with the program, and perceived areas of improvement. Retrospective review of 1,030 participants from November 2008 through May 2017. Data were obtained within an approved protocol (WRNMMC-EDO-2017-0004/# 876230). The program has shown growth in numbers of referrals, types of patient populations served, and patient visits. Patients report satisfaction with the program and endorse improvements in cognitive functions. This program model may benefit other military facilities looking to provide and assess novel therapeutic approaches.